Identifikasi Miskonsepsi Siswa SMA Pada Konsep Faktor-faktor yang Mempengaruhi Laju Reaksi - Muhammad Nazar; Sulastri Sulastri; Sri Winarni; Rakhmi Fitriana (Universitas Syiah Kuala, 2010)
This research aimed to identify misconception of senior high school students class XI in SMAN 1 Lhokseumawe in learning concept of factors that affect chemical reaction rate. The instrument used in this research was 20 multiple choice questions with reasons and equipped by CRI (Certainty of Response Index) which is used to measure the degree of certainty of students’ answers. There were 38 students as respondents in this research. The data shown that 13,16% of students held misconceptions relating to the effect of surface area on rates of reaction, 57,89% students held misconceptions relating to the effect of catalyst on rates of reaction, 57,89% students held misconceptions relating to the effect of temperature on rates of reaction, However there none of students misunderstood about the effect of reactant concentration and pressure to chemical reaction rate and most of them understood about the collision theory.